Prevalence of Noncardiac Findings in Patients Undergoing Cardiac Magnetic Resonance Imaging - Christopher W. May; William T. Mansfield; Andrew B. Landes; Adrian M. Moran (The Scientific World Journal)
Purpose. We sought to determine the prevalence of clinically significant non-cardiac abnormalities found in pediatric and adult patients undergoing cardiac magnetic resonance imaging (CMRI), and understand the impact of age on it’s occurrence. Methods. We retrospectively reviewed all patients undergoing CMRI between May 2004 and July 2007. Findings were considered significant if they required radiographic or clinical follow-up. Results. A total of 408 patients underwent CMRI during the study period. Twenty two (16%) pediatric patients (age < 19 years, n=135) were found to have a total of 22 non- cardiac abnormalities, 3 of which were clinically significant. Sixty four (23%) adult patients (age > 19 years, n=273) were found to have a total of 77 non-cardiac abnormalities, 33 of which were clinically significant. The prevalence of clinically significant non-cardiac abnormalities was 2% in the pediatric cohort and 11% in the adult cohort (P=0.05). Within the adult population, the prevalence of significant non-cardiac abnormalities increased with advancing age (P=0.05). Conclusions. In a population of unselected patients undergoing CMRI, unanticipated noncardiac abnormalities were frequently seen. A small number of these were significant, with the prevalence increasing with age.